Another Side of Balinese Excoticism Local Wisdom of the Muslim Community in Gelgel Village, Klungkung Regency, for Preserving Harmony between Religious Communities in Bali - Mahmud Arif; Zulkipli Lessy (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Bali is one of the most popular destinations chosen by foreign tourists for their visits to Indonesia. Accordingly, Bali often is the primary basis by which foreigners assess the entire nation. Tourist attention is drawn to Bali’s natural beauty and its cultural exoticism. They show various perspectives on Balinese religious and cultural life, those that are generally closely related to Hinduism and tourism. Through qualitative approach, this study aims to analysis the religious life of the Muslim communities in Bali for completing the various viewpoints while revealing another side of Balinese exoticism. The Gelgel village of Klungkung regency is a longestablished village inhabited by Muslims in the midst of strong influences of Hinduism. This village is of interest as the oldest Muslim village in Bali to be accorded designation as a banjar dinas, and even while having a slim territory. Notably, the people in the village are generally able to live peaceably side-by-side with adherents of other religions. This is enabled through local wisdoms that have allowed and encouraged harmony withcastle, temple, and Balinese customs.